Social Exclusion in Educational Discourse: an Analysis Based on a Program of Investigation - González Faraco, Juan Carlos; Luzón Trujillo, Antonio; Torres Sánchez, Mónica (Education Policy Analysis Archives, 2012)
The aim of this article is to show the theoretical and methodological foundations and stages of a research program that began more than ten years ago. This program emphasizes the complex relationship between social exclusion and education, and specifically between inclusion/exclusion and the governance of education in the framework of general policies and institutional practices. This program combines two analytical approaches: the approach of equity and the approach of knowledge, according to a political and cultural perspective. Both have epistemological and even ideological differentiated roots, but not contradictory. Both, in one way or another, are presented in three successive projects of this program’s research: 1. Education Governance and Social Integration and Exclusion in Europe (EGSIE); 2. Students at Risk of Educational Exclusion in Compulsory Secondary Education; 3. Social and Educational Exclusion in Children and Young People with AIDS. First, this program is based on the idea that certain changes in the governance of education can become mechanisms of inclusion/exclusion, in terms of social and cultural differentiation and stratification. It means that changes in educational policy can severely affect the ability of education to combat social exclusion. We argue about changes that concern the construction of social solidarity and political thinking in order to establish ways of understanding individuals, that is, their politics of knowledge. Using several concepts and categories such as transition and narration, we try to examine how the changes are produced or the principles that order politics, pedagogy, school success or even statistics are modified. In other words, how some systems of reason are introduced to play their role in an unequal field, including some rules of action that reward or punish, qualify or disqualify, integrate or marginalize individuals or groups.